Studi Perbandingan Metode Sampling Bor Riap dengan Disk untuk Pengukuran Proporsi dan Dimensi Serat Kayu Sengon Salomon (Paraserianthes falcataria, (L.) Nielsen) Comparative Study of Two Types Sampling Method for Measuring Cell Proportion and Fiber Dimension on Sengon Salomon Wood (Paraserianthes falcataria (L.) Nielsen) - Harry Praptoyo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
The objective of this research was to determine the differentiation on the measurement result of cell proportion and fiber dimension that caused by the different of sampling methods. The research was conducted at the Laboratory of Wood Structure and Properties, Faculty of Forestry, Gadjah Mada University.The research designed with completely random design composed by factorial experiment, which considered two factors, namely: 1) Sampling methods: disk method and drill method, and 2) Radial distribution: center/pitch, center-bark and near bark. Analysis of variance was conducted in order to evaluate the variation in all data of two factors mentioned above. The relationship between sampling method and radial distribution was also evaluated. The data variables were: fiber length, cell diameter, lumen diameter, cell wall thickness, and the proportion of vessel, rays, fiber and parenchyma. The observation on fiber length was conducted by using light microscope or scanning electron microscope. The observation on cell proportion was conducted by using photomicroscope and dot grid.The results of the research showed that the different of sampling methods have not any influenced to the measurement result of cell proportion and fiber dimension on Sengon wood. Whereas the radial distribution of wood has significant influenced in fiber dimension, especially in fiber length and cell wall thickness, but in cell proportion, radial distribution has not influenced.